2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6748299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stearic acid and thermal treatment on morphology and dielectric properties of UHMWPE/POSS composites prepared by ball milling

Abstract: For the last decade, there has been lots of interest in the development of nanodielectrics as these materials may present superior dielectric properties when compared to traditional composites. However, the success of these materials relies on a proper dispersion of nanofillers within the matrix. In this work, UHMWPE/POSS composite of Ultra-High-Molecular Weight PolyEthylene (UHMWPE) with 5% wt Octaisobutyl Polyhedral Oligomeric SilSesquioxanes (POSS) was prepared by ball milling. In order to enhance the dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Joshi et al showed that addition of octamethylsilsesquioxane to HDPE at various loadings had little impact on crystallinity level of the polymer, however it mediated its crystallite size [ 23 ]. Guo et al also suggested that when applying octa( iso butyl)silsesquioxane for UHMWPE, the additive segregated on the spherulite interfaces, where most of the polymer amorphous phase is located [ 37 ]. The non-linear relationship between the SSQ additive loading and the crystallinity levels of PE can be explained on the basis of two levels of dispersion of the additives, where at higher loadings more agglomerates form and the less numerous, large particles of the additive provide less nucleation sites for the crystallizing polymer [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joshi et al showed that addition of octamethylsilsesquioxane to HDPE at various loadings had little impact on crystallinity level of the polymer, however it mediated its crystallite size [ 23 ]. Guo et al also suggested that when applying octa( iso butyl)silsesquioxane for UHMWPE, the additive segregated on the spherulite interfaces, where most of the polymer amorphous phase is located [ 37 ]. The non-linear relationship between the SSQ additive loading and the crystallinity levels of PE can be explained on the basis of two levels of dispersion of the additives, where at higher loadings more agglomerates form and the less numerous, large particles of the additive provide less nucleation sites for the crystallizing polymer [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As organosilicon hybrid compounds, SSQs tend to improve thermal stability of polymer matrices they are introduced into, but also modify materials rheology (e.g., as plasticizers or thixotropic agents) or improve mechanical properties, such as tensile or flexural modulus, tensile strength, heat deflection temperature. Different structures have been tested, including homo-(R n [SiO 1.5 ] n ) and heterosubstituted (R n-m R’ m [SiO 1.5 ] n ) systems, bearing either alkyl [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], alkenyl [ 41 , 48 ], aryl [ 24 , 25 , 26 ], or other functional groups [ 26 , 41 , 49 , 50 , 51 , 52 ], introduced mostly by condensation, hydrosilylation, or substitution reactions. It has been proven that a choice of introduced functional groups plays a major role in miscibility of silsesquioxanes and polymer matrix and the additive tendency towards agglomeration, but also the processing method and parameters have an impact on the obtained additive dispersion in the final composite or nanocomposite [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation